Enhancement of dispersion and bonding of graphene-polymer through wet transfer of functionalized graphene oxide - F. Sharif; M. Moazzami Gudarzi (eXPRESS Polymer Letters, 2012)
Dispersion of nanomaterials in polymeric matrices plays an important role in determining the final properties of the composites. Dispersion in nano scale, and especially in single layers, provides best opportunity for bonding. In this study, we propose that by proper functionalization and mixing strategy of graphene its dispersion, and bonding to the polymeric matrix can be improved. We then apply this strategy to graphene-epoxy system by amino functionalization of graphene oxide (GO). The process included two phase extraction, and resulted in better dispersion and higher loading of graphene in epoxy matrix. Rheological evaluation of different graphene-epoxy dispersions showed a rheological percolation threshold of 0.2 vol% which is an indication of highly dispersed nanosheets. Observation of the samples by optical microscopy, scanning electron microscopy (SEM), and atomic force microscopy (AFM), showed dispersion homogeneity of the sheets at micro and nano scales. Study of graphene-epoxy composites showed good bonding between graphene and epoxy. Mechanical properties of the samples were consistent with theoretical predictions for ideal composites indicating molecular level dispersion and good bonding between nanosheets and epoxy matrix.